Application of Symbolic Language and Pattern Innovation of Chaoshan Peach Cake Mold in Paper Packaging Design - Jiahang Chen (BioResources)
To explore the symbolic language of the Chaoshan peach cake mold and its innovative applications in modern design, the material form and cultural connotations of the mold patterns were analyzed from a semiotic perspective. Through a symbolic language of the primary pattern elements, the essence of the traditional culture they embody was revealed. Building on this analysis, the generative rules of shape grammar were applied to creatively reinterpret and recombine these traditional pattern elements, resulting in a set of innovative designs that retain the essence of traditional culture while incorporating modern design aesthetics. Furthermore, these innovative patterns were implemented in paper packaging design, and their effectiveness was validated through product evaluation. Through an in-depth exploration and innovative application of the symbolic language of the Chaoshan peach cake mold, a successful fusion of traditional cultural symbols and contemporary design concepts was achieved. This approach provides a new pathway for the inheritance and innovation of Chaoshan peach cake mold culture and offers insights into the modern transformation of other traditional cultures.